Scaffolding SETS for Coloid Material on Yoghurt Contens - Khodijah Lestari; Eka Yusmaita (Universitas Negeri Padang, 2023)
The purpose of this study is to describe the scaffolding applied to the chemistry learning process on colloidal material in the context of yogurt using the SETS approach. Scaffolding is a learning strategy in which the teacher provides assistance to students in solving a problem in the learning process. Yogurt is an example of a type of colloid with a type of colloid emulsion, and is a form of application of the colloid concept. This type of research is a quantitative descriptive research. The subjects in the study were 20 class XII students of SMAN 1 Padangbolak. The results of the analysis show that the existence of scaffolding given by the teacher, especially in colloid learning, can help students understand learning, which can be proven by the average student score of 82,9.